Hannah Arendt: Kekerasan bukan Tindakan Politik, Namun bukan tanpa Resiko - Benyamin Molan (Respons: Jurnal Etika Sosial, 2009)
Abstract: This paper considers the implication of Hannah Arendt’s criticism of the relationship between violence and politics. For some political theorists and philosophers, it is taken for granted, that violence and politics are inextricably intertwined. For Arendt, it is crucial to  keep the two clearly and distinctly apart. After arguing for a tripartite division between the human activities of labor, work and action, Arendt identifies the politics as the part of action, and the violence as the part of labor and work. This is the way Arendt argues to keep the politics and the violence clearly apart.Kata Kunci: Kekerasan, politik,  kerja (labor), karya (work), tindakan (action), kebebasan